Designing Electronic Kanban To Reduce Lead Time On Cone Assembly Line In Pt Xyz - Nadhifah Aqilah Nugraha; Dida Diah Damayanti; Widia Juliani (eProceedings of Engineering, 2020)
Abstract— Airplanes manufacturing are growing along with the increasing demand from consumers. PT XYZ is a manufacturing company of aircraft included the design and development, manufacture, assembly, and services of aircraft. The helicopter's tail called Tailboom is a product of the helicopter division, where the Tailboom assembly line is a pull system. Based on observations of existing conditions that occur at PT XYZ, production is still unable to meet demands of consumers, Lead Time occurs greater than the plan agreed upon by the consumers. In the assembly process, each work station experiences a lack of parts and component needed to assemble. This happens because of the delay in getting the required part information and there is no warning about the availability of parts needed, it makes some parts unavailable in assembly warehouse. The lack of parts and components from the previous work station causes the assembly process to stop and the assembly line also stops at the next station. In its completion, the production time was late and not on schedule. In resolving these problems, controlling process is needed, which is controlling the assembly line to get all components and sub-assembly in the right amount and at the right time. This study applies one of Just In Time tools, namely Kanban and automation should be added as efficiently and effectively communication line becomes Electronic Kanban. The problem can be solved by reducing buffer such as waiting time and idle time. The proposed results of controlling the assembly line of Tailboom result in a smooth assembly line without waiting, reduced lead time and achieving production time according to the schedule agreement with the consumers. Keywords— Kanban, E-Kanban, Lead Time, Pull System. Abstrakt— Manufaktur pesawat terbang tumbuh seiring dengan meningkatnya permintaan dari konsumen. PT XYZ adalah perusahaan manufaktur pesawat yang mencakup dalam desain dan pengembangan, pembuatan, perakitan, dan perawatan pesawat. Ekor helikopter yang disebut Tailboom adalah produk dari divisi helikopter, dengan lini perakitan Tailboom adalah sistem tarik. Berdasarkan pengamatan terhadap kondisi saat ini di PT XYZ, produksi masih belum dapat memenuhi permintaan konsumen, Lead Time terjadi lebih besar dari rencana yang disepakati oleh konsumen. Dalam proses perakitan, setiap stasiun kerja mengalami kekurangan komponen yang dibutuhkan untuk merakit. Hal ini terjadi karena keterlambatan dalam mendapatkan informasi bagian yang diperlukan dan tidak ada peringatan tentang ketersediaan suku cadang yang dibutuhkan, hal ini membuat beberapa komponen tidak tersedia di gudang perakitan. Kurangnya komponen dari stasiun kerja sebelumnya menyebabkan proses perakitan berhenti dan lini perakitan juga terhenti di stasiun berikutnya. Sehingga, waktu produksi terlambat dan tidak sesuai jadwal. Dalam menyelesaikan masalah ini, diperlukan adanya proses pengendalian, yaitu mengendalikan lini perakitan untuk mendapatkan semua komponen dan sub-perakitan dalam jumlah yang tepat dan pada waktu yang tepat. Penelitian ini menerapkan salah satu alat Just In Time, yaitu Kanban dan ditambahkan otomatisasi sebagai jalur komunikasi yang lebih efisien dan efektif menjadi Elektronik Kanban. Masalah ini dapat diselesaikan dengan mengurangi buffer seperti waktu tunggu dan waktu idle. Hasil yang diusulkan untuk mengontrol jalur perakitan Tailboom menghasilkan jalur perakitan yang lancar tanpa menunggu, mengurangi lead time dan mencapai waktu produksi sesuai dengan perjanjian jadwal dengan konsumen. Kata Kunci- Kanban, E-Kanban, Lead Time, Sistem Tar